2015
DOI: 10.1007/s10661-015-4840-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of agricultural pesticides in water, sediment, and fish from Owan River, Edo State, Nigeria

Abstract: The distribution of pesticides in water, sediments, Clarias gariepinus, and Tilapia zilli from the Owan River was investigated to evaluate the pollution status and potential hazard in the river system. A total of 16 pesticides were analyzed using gas chromatography (GC) equipped with electron capture detector (ECD). The concentration of pesticide residues ranged from ND to 0.43 μg/l for water samples, 0.82 to 2.14 μg/kg/dw for sediment, 0.04 to 2.34 μg/kg/ww for C. gariepinus, and 0.02 to 1.73 μg/kg/ww for T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…It was clearly reported that minute concentrations of pesticides are toxic to biological organisms and they threaten ecosystem integrity due to their stable structure and lipophilic character. They also tend to bioconcentrate, bioaccumulate and biomagnify, and are transferred to higher trophic levels through several food chains and may lead to toxicity in non-target organisms like vertebrates and non-vertebrates and even in humans [10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…It was clearly reported that minute concentrations of pesticides are toxic to biological organisms and they threaten ecosystem integrity due to their stable structure and lipophilic character. They also tend to bioconcentrate, bioaccumulate and biomagnify, and are transferred to higher trophic levels through several food chains and may lead to toxicity in non-target organisms like vertebrates and non-vertebrates and even in humans [10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Dietary pesticide risks can be estimated through well-established indices and defined and used by US Environmental Protection Agency (EPA) [ When no specific MRL is published, a 0.01 mg/kg value is applied [8]. Additionally, hazard quotients (HQs)-which measure the potential exposure for developing non-carcinogenic health effects-may be calculated using several assumptions [65].…”
Section: Human Health Risksmentioning
confidence: 99%
“…The lack of ecological risk inventory for acute and chronic adverse effects of organic pollutants in the aquatic environment demands precautionary measures (Deblonde et al, 2011;Gavrilescu et al, 2015). Ecological risk/hazard assessment is to investigate the changes in aquatic species as result of exposure to environmental stressors, such as organic contaminants (Ogbeide et al, 2015). The tracking of ecological risks of organic pollutants is of critical importance to regulate the PSs and CECs and the adverse effects may accumulate continuously to cause irreversible molecular damages to the aquatic ecosystems (Jjemba, 2006).…”
Section: Ecological Risks Of Pahs Dehp and Ppcpsmentioning
confidence: 99%